2013
DOI: 10.3762/bjoc.9.33
|View full text |Cite
|
Sign up to set email alerts
|

Towards a biocompatible artificial lung: Covalent functionalization of poly(4-methylpent-1-ene) (TPX) with cRGD pentapeptide

Abstract: SummaryCovalent multistep coating of poly(methylpentene), the membrane material in lung ventilators, by using a copper-free “click” approach with a modified cyclic RGD peptide, leads to a highly biocompatible poly(methylpentene) surface. The resulting modified membrane preserves the required excellent gas-flow properties while being densely seeded with lung endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…34 For the design of a biohybrid lung, PDMS has excellent gas permeability and hemocompatibility and is amenable to various surface modifications. 1,2,12,16,17,36 We found that ECs in dynamic culture were proliferative and reached confluence on PDMS membranes within 3 days, as confirmed by immunocytochemistry (Fig. 2f).…”
Section: Discussionsupporting
confidence: 61%
“…34 For the design of a biohybrid lung, PDMS has excellent gas permeability and hemocompatibility and is amenable to various surface modifications. 1,2,12,16,17,36 We found that ECs in dynamic culture were proliferative and reached confluence on PDMS membranes within 3 days, as confirmed by immunocytochemistry (Fig. 2f).…”
Section: Discussionsupporting
confidence: 61%
“…Perfluorophenyl azides form highly reactive nitrene intermediates under UV irradiation, and the latter readily undergo C─H insertion reactions with hydrocarbon‐based materials . Only a few studies report on using this methodology for surface functionalization of porous polymeric scaffolds, eg, melt‐blown poly(butylene terephthalate) (PBT) nonwoven fiber meshes or poly(4‐methyl‐1‐pentene) membranes . It was envisioned that the versatile PFPA chemistry can be used by inserting the perfluorophenyl nitrene intermediate into the aliphatic groups of PPDO.…”
Section: Introductionmentioning
confidence: 99%
“…17 Only a few studies report on using this methodology for surface functionalization of porous polymeric scaffolds, eg, meltblown poly(butylene terephthalate) (PBT) nonwoven fiber meshes 18 or poly(4-methyl-1-pentene) membranes. 19 It was envisioned that the versatile PFPA chemistry can be used by inserting the perfluorophenyl nitrene intermediate into the aliphatic groups of PPDO. As the reaction can be performed in a nonaqueous environment, it was hypothesized that polymer hydrolysis can be avoided with this strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Colonization with human endothelial progenitor cells on heparin/albumin-coated PMP membranes has also been shown. 30 Functionalization of the PMP surface by the covalent coupling of cell type-specific peptide sequences (e.g. cRGD, cyclic arginine-glycine asparagine) by means of copper-free "click" chemistry 30 or by coating with titanium oxide improved the adhesion of endothelial cells.…”
Section: Analysis and Design Of Biocompatible Membrane And System Surmentioning
confidence: 99%